The Role of AI in Digital Supply Chain Transformation in The Era of Trade Wars: Bibliometrics Analysis 2021-2025 - Ita Dwi Septiani (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Purpose – This study aims to examine the development, structure, and research focus of the literature on supply chain transformation in the context of global disruptions Methodology – This research applies a quantitative bibliometric analysis based on data retrieved from the Scopus database and VOSviewer to identify publication trends, citation patterns, international collaboration, and thematic clusters Findings – The results indicate a steady growth in publications, highlighting the increasing academic attention to supply chain resilience and operational risk management. Keyword co-occurrence analysis reveals four dominant research themes Research limitations – This study only used data from the Scopus database in the period 2021-2025 Practical implications – Highlight the importance of combining operational strategies with digital capabilities, expanding supplier sources, and increasing the flexibility of supply chain networks to address ongoing uncertainty.